Working terms - Thomas, Chris; Attenburrow, Andy (Nalgo ; Oceania Media Network [distributor], 1984)
Looks into problems created in a large institution (Tameside Metropolitan Burough Council) by the introduction of new advanced technologies when the necessary re-training is not provided.